MGH: a genome hub for the medicinal plant maca (Lepidium meyenii). (19th October 2018) - Chen, Junhao; Zhang, Jiawei; Lin, Meigui; Dong, Wei; Guo, Xinyue; Dong, Yang; Wang, Zhengjia; Zhang, Liangsheng; Chen, Fei
Abstract: Maca ( Lepidium meyenii ), a Brassicaceae herb plant originated from Andean mountains, has attracted wide interests due to its unique health benefits in reproduction and fertility. Because of its adaptation to the 4000 m high-altitude harsh environment, maca is attracting more and more attention from both crop breeders and basic biologists. After our previous release of the maca genome sequence, there's a growing need to store, query, analyze and integrate various maca resources efficiently. Here, we created Maca Genome Hub (MGH), a genomics and genetics database of maca. Currently, the MGH V1.0 harbors the genome sequence, predicted coding sequences and protein sequences, various annotations, markers and expression data. For the maca research community, we also provided the publications, researchers and related news. MGH is designed to enable users' easy access to analyze, retrieve and visualize the genomic or genetic information through a series of online tools, including the Basic Local Alignment Search Tool, the JBrowse, the query system, the synteny tool and the data downloads. These integrated heterogeneous data, tools and interfaces in MGH allow efficient mining of the latest genomics and genetics data. We hope that MGH will accelerate the research and development in maca.